Perencanaan dan Evaluasi dalam Perubahan SDM Lembaga Dakwah - Muhammad Yudha Ardiansyah; Cecep Castrawijaya (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Human resource (HR) development is an important aspect for the sustainability of Islamic missionary institutions. HR planning aims to ensure the availability of competent Islamic missionary personnel in accordance with the organization's needs. Evaluation is necessary to assess the effectiveness of HR performance in achieving Islamic missionary goals. This study uses qualitative methods with a documentary analysis approach. The results of the study indicate that good HR planning includes needs analysis, recruitment, development, and training of HR managers. HR assessment is an important tool for evaluating performance and improving the effectiveness of Islamic missionary activities. However, challenges in HR evaluation include the lack of an objective evaluation system, limited resources, and resistance to change. Wise HR change management can improve the quality of Islamic missionary activities, expand their reach, and increase the effectiveness of Islamic missionary institutions in facing today's challenges. This study recommends the importance of an objective evaluation system, better resource management, and continuous training to improve the competence of HR managers in Islamic missionary institutions.